Analisis Sistem Pengelolaan Barang Milik Daerah Pada Pemerintah Kabupaten Gorontalo - Ali, Rukiah Rahman; Karamoy, Herman; Warongan, Jessy (Universitas Sam Ratulangi, 2017)
Abstract. Management of the local Asset must be implemented properly in order to give an idea of the richness of the area, and can be used for basic financial statements. This study aims at analyzing the management system of Regional Property at Gorontalo District Government. This is a qualitative research study with a case study approach. The data were obtained through in-depth interview, observation and document analysis. The semi-structured and in-depth interviews were conducted for 45 to 60 minutes. The triangulation method was used to test the validity or credibility of the data and data sources. The interviews were transcribed and were analyzed by coding or giving themes and making a conceptualization with scientific statements. Then, the results of the interpretation were summarized in the narrative text. The result of the research shows that there are some obstacles in the management of Regional Property in Gorontalo Regency Government. The absence of regulation is in the form of local regulations and SOP. Lack of knowledge and understanding of how to use the property and of RP, the planning for required property needs is constrained by the limited budget so that the required property cannot be obtained, the issue of security and maintenance is emerged from the absence of representative warehouses for property storage, evidence of ownership in the form of certificates that are still on behalf of the Ministry, removal is constrained by the unknown of the inexistence of property.Keywords: RP Management, RP Regulation, RP Problems.Abstrak. Pengelolaan Barang Milik Daerah harus dilaksanakan dengan baik agar dapat memberikan gambaran tentang kekayaan daerah, serta dapat digunakan untuk dasar penyusunan laporan keuangan. Penelitian ini bertujuan menganalisis sistem Pengelolaan Barang Milik Daerah pada Pemerintah Kabupaten Gorontalo. Metode penelitian menggunakan kualitatif dengan pendekatan studi kasus. Data diperoleh melalui teknik wawancara mendalam, pengamatan dan studi dokumentasi. Wawancara menggunakan In-depth interview jenis semi terstruktur Â dilakukan selama 45 hingga 60 menit. Metode triangulasi digunakan dalam pengujian validitas atau kredibilitas data dan sumber data. Data transkrip yang diuraikan dari hasil wawancara dianalisis dengan metode analisis kemudian diberi tema/ coding dan dilakukan konseptualisasi pernyataan ilmiah. Hasil interpretasi disimpulkan dalam teks naratif. Hasil penelitian menunjukkan terdapat beberapa kendala dalam pengelolaan Barang Milik Daerah di Pemerintah Kabupaten Gorontalo. Belum adanya regulasi berupa Perda dan SOP, minimnya pengetahuan dan pemahaman Pengguna Barang tentang pengelolaan BMD, perencanaan kebutuhan barang terkendala kondisi anggaran yang terbatas sehingga ada kebutuhan yang seharusnya diadakan tapi belum bisa direalisasikan, pengamanan dan pemeliharaan terkendala belum adanya gudang yang representatif untuk penyimpanan barang, bukti kepemilikan berupa sertifikat yang masih atas nama Kementerian, penghapusan terkendala adanya barang yang sudah tidak diketahui lagi keberadaannya.Kata Kunci: Pengelolaan BMD, RegulasiÂ BMD, Masalah BMD.